Impact of chemotherapy on antioxidant micronutrient levels in patients with mature lymphoid malignancies - Akunwata, Chima Uzoma; Olaniyi, John Ayodele (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Cancer treatments are now intense and are associated with nutritional deficiencies. The nutritional status of a patient may influence the tolerability of chemotherapy. Aim. We investigated the effects of chemotherapy on serum levels of trace elements (copper, iron, manganese, selenium, and zinc) and vitamins (A, C, and E) in patients with mature lymphoid malignancies (MLMs) at diagnosis and after 3 months. Material and methods. A case-control study of adults diagnosed with and treated for various MLMs. Thirty-nine cases and 39 age and sex-matched controls were recruited into this study. Venous blood samples were collected from the controls, cases at baseline and after 3 months of chemotherapy. Trace elements were determined by AAS while vitamins were determined by HPLC. Results. The levels of trace elements and antioxidant vitamins A and E were significantly higher (p<0.001) in cases than in controls while vitamin C was lower in cases compared to controls (p=0.005). After 3 months of treatment, 28 patients were available for analysis. There was a significant decline (p<0.001) in all the levels of trace elements and vitamins after chemotherapy. Conclusion. Chemotherapy is associated with a significant reduction in antioxidants levels in patients with MLMs.
Keywords: antioxidant micronutrients; chemotherapy; haematologic malignancies